THE EFFECT OF RADIATION ON DEVELOPMENT OF ROOT-KNOT NEMATODES - A. Damianova (Российский паразитологический журнал, 2016)
Root-knot nematodes (Meloidogyne spp.) are one of the most important plant parasitic nematodes of great economic importance which reduce the quantity and the quality of the yields of many cultivated and wild plants everywhere (in tropical, subtropical and temperate regions). The objectives of the study were to investigate the changes in the Meloidogyne arenaria and its host Tiny Tim tomato plant under radiation influence The influence of various doses of γ-irradiation (90, 700 and 1800 mGy) on cv. Tiny Tim tomato plants and developing eggs sacs of root-knot nematode Meloidogyne arenaria were investigated. Ionizing radiations of tomato seeds by low dose (90 mGy) stimulate development of plants. High doses of γ-irradiation (700 and 1800 mGy) suppress development (height, root and shoot weight) of tomato plants. High irradiation doses (700 and 1800 mGy) retarded the growth of nematodes. Metric characteristics of M. arenaria females, mainly body size, were smaller. The highest experimental dose (1800 mGy) prevented the development of females of M. arenaria (J4) to mature forms. A change of female to male ratio under the influence of γ- ionizing radiation has been observed, resulting in a decrease in males. These results show aspects for future research into the application of γ-irradiation in management of root-knot nematodes